2019
DOI: 10.1101/674226
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Leveraging eQTLs to identify individual-level tissue of interest for a complex trait

Abstract: AbstractGenetic predisposition for complex traits often acts through multiple tissues at different time points during development. As a simple example, the genetic predisposition for obesity could be manifested either through inherited variants that control metabolism through regulation of genes expressed in the brain, or that control fat storage through dysregulation of genes expressed in adipose tissue, or both. Here we describe a statistical approach that leverages tissue-sp… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…For example, Majumdar et al showed that tissue-specific eQTLs can be employed to generate tissue polygenic risk scores for complex traits. 54 Similarly, other groups have shown enrichments of complex traits for biologically relevant tissues by using colocalization or mediation approaches on eQTL data. 4,53,55 However, as a result of the inability of existing methods to fully evaluate allelic heterogeneity and LD, the extent of tissue specificity of eQTLs has not been previously fully explored or harnessed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Majumdar et al showed that tissue-specific eQTLs can be employed to generate tissue polygenic risk scores for complex traits. 54 Similarly, other groups have shown enrichments of complex traits for biologically relevant tissues by using colocalization or mediation approaches on eQTL data. 4,53,55 However, as a result of the inability of existing methods to fully evaluate allelic heterogeneity and LD, the extent of tissue specificity of eQTLs has not been previously fully explored or harnessed.…”
Section: Discussionmentioning
confidence: 99%
“…Several investigators have shied away from recommending the use of eQTL information to prioritize target tissues in GWAS, 42,50 citing the tissue-sharing of cis-eQTLs in a large fraction of trait associations as one reason. 51 Recent work by us 52 and others 4,53,54 has demonstrated the existence of tissue-specific eQTLs and shown potential for leveraging those eQTLs to understand broad patterns of tissue enrichment for human complex traits. For example, Majumdar et al showed that tissue-specific eQTLs can be employed to generate tissue polygenic risk scores for complex traits.…”
Section: Discussionmentioning
confidence: 99%
“…Variations of canonical correlation analysis (CCA) have characterized relationships between depressive symptoms and neuroimaging measures ( 58 ), and hierarchical clustering on resting-state fMRI measures have identified groups of depressed patients and their differential network dysfunctions ( 59 ), and machine learning methods have been used to cluster longitudinal responses to antidepressants to identify stable treatment response classes ( 60 ). In the future, these may be integrated with multi-omics for example, transcriptome-wide association (TWAS) approaches have begun to identify depression subtypes driven by brain and adipose tissue-specific gene expression ( 61 ).…”
Section: Using Manifestations To Understand Etiologymentioning
confidence: 99%